Implementasi Teknologi Informasi untuk Meningkatan Mutu Layanan Perpustakaan - Muslina Muslina (Al-Ma'mun: Jurnal Kajian Kepustakawanan dan Informasi, 2020)
Library services in this case the library services include circulation services, reference services, journal / magazine services, multimedia services, internet services and computer stations. These services must follow technological developments in providing information in accordance with the needs of users. IT in libraries is often a benchmark of progress and modernization of a library. The goal of information technology in improving service quality is easy, fast and accurate access through telecommunications networks (LAN, WAN , and internet). This article tries to explain what and how the implementation of information technology to improve the quality of library services. The conclusion is the implementation of information technology in improving the quality of library services is the application of technology used in conveying and processing information to improve quality or standards that must be achieved in the main activities in each library. services such as application to circulation services, reference services, periodical journal or magazine services, multimedia or audio-visual services, internet and computer station services, security services and procurement services.